EXPERIMENTAL DESIGN APPROACH FOR STUDYING OVERHANGING FEATURES IN SELECTIVE LASER MELTING - Patterson, A.E.; Messimer, S.L.; Farrington, P.A.; Carmen, C.L.; Kendrick, J.T. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
As additive manufacturing (AM) processes become more refined and widely used, it is essential for engineers and designers to understand the processes in order to effectively use them within manufacturing systems; however, most of the existing methods for analyzing AM processes are too complex and specialized for use in practice. This study proposes a simple technique to derive information about the behavior of unsupported overhanging features in parts made using selective laser melting (SLM) using a first-principles finite element model and factorial experiment. This method can be used to assist with design decisions without production of prototypes, resulting in improved design and reduced cost. The case study presented examined five factors (laser power, laser spot size, scan speed, feature thickness, and the use of support material) in a 25 full-factorial arrangement with two stress and two deformation responses. An analysis of variance (ANOVA) was completed on the results, showing the significance of both the factors and the interactions between them. Two materials were studied (Ti-6Al-4V and 316L stainless steel). The results were compared to some similar stress and deformation results from experimental literature and were found to match well with the greatly simplified approach.